Contribution Of Refinery Carbon Dioxide Emission To Global Warming - R Desrina (Scientific Contributions Oil and Gas, 2010)
The energy sector, including petroleum refining, is likely to feature in any legislation aimed at reducing CO2 emissions. It seems that petroleum refinery contributes relatively small amount of CO2 emission compared to other sectors such as transportations. Recently, through presidential speech in Copenhagen, government of Indonesia has committed to reduce CO2 emission to 26 percent in the year of 2020. Many technologies can be used for reducing CO2 emission in refinery. These technologies include fuel replacement, gasification of heavy residue which leads to single point CO2 capture, and CO2 equestration. This paper tries to discuss how far CO2 emissions contributed by refinery and possible actions that can be managed on the refinery to significantly reduce CO2 emissions